Neutralization of viral infectivity by zebrafish c-reactive protein isoforms. (November 2017) - Bello-Perez, Melissa; Falco, Alberto; Medina-Gali, Regla; Pereiro, Patricia; Encinar, Jose Antonio; Novoa, Beatriz; Perez, Luis; Coll, Julio
Highlights: Seven C-reactive protein isoforms were studied in zebrafish. Transcript ( crp ) and protein (CRP) levels changed heterogeneously after viral infections. Some of the crp1-7 /CRP1-7 neutralized and protected against viral infections. Most anti-viral effects were due to crp2 /CRP2 and crp5 /CRP5. Abstract: This work explores the unexpected in vivo and in vitro anti-viral functions of the seven c-reactive protein ( crp1-7 ) genes of zebrafish ( Danio rerio ). First results showed heterogeneous crp1-7 transcript levels in healthy wild-type zebrafish tissues and organs and how those levels heterogeneously changed not only after bacterial but also after viral infections, including those in adaptive immunity-deficient rag1 −/− mutants. As shown by microarray hybridization and proteomic techniques, crp2/ CRP2 and crp5/ CRP5 transcripts/proteins were among the most modulated during in vivo viral infection situations including the highest responses in the absence of adaptive immunity. In contrast crp1/ CRP1/and crp7 /CRP7 very often remained unmodulated. All evidences suggested that zebrafish crp2-6 /CRP2-6 may have in vivo anti-viral activities in addition to their well known anti-bacterial and/or physiological functions in mammalians. Confirming those expectations, in vitro neutralization and in vivo protection against spring viremia carp virus (SVCV) infections were demonstrated by crp2-6/ CRP2-6 using crp1-7 transfected and/or CRP1-7-enriched supernatant-treated fish cells and crp2-5 -injected one-cell stage embryo eggs, respectively. All these findings discovered a crp1-7 /CRP1-7 primitive anti-viral functional diversity.These findings may help to study similar functions on the one-gene-coded human CRP, which is widely used as a clinical biomarker for bacterial infections, tissue inflammation and coronary heart diseases.